SH_OBERGERICHT 40/2002/32 vom 14. März 2003 - Sh Obergericht (2003)
Art. 271 Abs. 1 Ziff. 2 und Abs. 2 sowie Art. 274 Abs. 2 Ziff. 2 SchKG. | Verarrestierung künftiger Unterhaltsbeiträge beim Fluchtarrest